Pemberdayaan Masyarakat melalui Diversifikasi Produk Perikanan: Pelatihan Nugget Ikan sebagai Upaya Pengembangan Ekonomi Kreatif di Desa Karang, Langsa Baro, Aceh. - Dewi Rosa Indah; Rahmi Meutia; Meutia Dewi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This Community Partnership Program (PKM) aims to empower non-productive community groups through fish nugget production training as an effort to develop the creative economy and strengthen food security in Karang Anyar Village, Langsa Baro District, Aceh. The village has abundant fishery resources; however, their utilization has not been optimal because most residents sell fish only in fresh form with relatively low economic value. In addition, the community’s skills in processing fishery products into value-added products are still limited. The implementation method used a participatory approach through observation, socialization, education, training, direct practice, and mentoring stages. The training activities included the selection of quality fish raw materials, fish nugget processing techniques, packaging methods, and basic product marketing. The target participants were non-productive community groups, especially housewives, so that they could develop home-based businesses using processed fishery products. The results of the program showed that participants had high enthusiasm and were able to independently practice the production of fish nuggets. This program successfully improved community knowledge and skills in fishery product diversification and encouraged entrepreneurial interest based on the creative economy. In addition, the fish nuggets produced can serve as nutritious local food alternatives while also creating opportunities to increase community income. Therefore, this PKM activity has provided positive impacts in improving community skills, supporting food security, and encouraging the development of a creative economy based on local potential in Karang Anyar Village, Langsa Baro District, Aceh.